2021
DOI: 10.1007/s00300-021-02951-z
|View full text |Cite
|
Sign up to set email alerts
|

Could Norwegian fjords serve as an analogue for the future of the Svalbard fjords? State and fate of high latitude fjords in the face of progressive “atlantification”

Abstract: Benthic foraminifera are one of the most widely and abundantly distributed organisms in the fjords of Svalbard and Norway. Due to their short life span and quick reactivity to environmental changes they can be used as indicators of the “atlantification” process. Here, we compare the benthic foraminifera assemblages along the latitudinal gradient, from the fjords of northern Svalbard to southern Norway to assess whether the “atlantification” process may homogenise the foraminiferal assemblages in terms of their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
0
5
2
Order By: Relevance
“…On the other hand, recent model projections indicated low mean habitat loss of benthic macrofauna under recent climate changes, which questions the vulnerability of Arctic benthos to atlantification 98 . This stands in clear opposition to the morphological observations that testate foraminifera communities from Svalbard fjords revealed significant changes, both in terms of abundance and species composition, related to atlantification 99 . Our study confirms the impact of AW on foraminiferal communities, suggesting that AW is one of the primary factors shaping the benthic foraminifera assemblages and thus foraminifera may be potential indicators of atlantification.…”
Section: Influence Of Atlantification On Foraminifera Communitycontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recent model projections indicated low mean habitat loss of benthic macrofauna under recent climate changes, which questions the vulnerability of Arctic benthos to atlantification 98 . This stands in clear opposition to the morphological observations that testate foraminifera communities from Svalbard fjords revealed significant changes, both in terms of abundance and species composition, related to atlantification 99 . Our study confirms the impact of AW on foraminiferal communities, suggesting that AW is one of the primary factors shaping the benthic foraminifera assemblages and thus foraminifera may be potential indicators of atlantification.…”
Section: Influence Of Atlantification On Foraminifera Communitycontrasting
confidence: 99%
“…One of the major signs of atlantification is the northward shift of boreal species, the trend observed in the case of zooplankton, fish, and benthic organisms 97 . A recent morphological study of Svalbard foraminifera revealed the presence of boreal species Melonis affinis in the northern part of the archipelago 99 . Reophax sp.…”
Section: Influence Of Atlantification On Foraminifera Communitymentioning
confidence: 99%
“…On the other hand, recent model projections indicated low mean habitat loss of benthic macrofauna under recent climate changes, which questions the vulnerability of Arctic benthos to atlantification (Renaud et al, 2019). This stands in clear opposition to the morphological observations that testate foraminifera communities from Svalbard fjords revealed significant changes, both in terms of abundance and species composition, related to the influence of AW (Kujawa et al, 2021). Our study confirms the impact of AW on foraminiferal communities, suggesting that AW is one of the primary factors shaping the benthic foraminifera assemblages and thus foraminifera may be potential indicators of atlantification.…”
Section: Influence Of Aw On Foraminifera Communitycontrasting
confidence: 93%
“…A recent morphological study of Svalbard foraminifera revealed the presence of boreal species Melonis affinis in the northern part of the archipelago (Kujawa et al, 2021). Reophax sp.…”
Section: Influence Of Aw On Foraminifera Communitymentioning
confidence: 99%
“…https://doi.org/10.1017/cft.2023.1 Published online by Cambridge University PressAccepted ManuscriptNorway due to the greater direct human influence on the continent(Kujawa et al, 2021).…”
mentioning
confidence: 99%